William Saunders journal - Saunders, William, 1822-1900.
Journal (1898 December 20-1899 January 10) kept by Saunders recording his horticultural activities.
Microfilm and positive photocopy produced from photocopy in U.S. Dept. of Agriculture Library.
Horticulturist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Horticulture; Horticulturists